Production and sensory evaluation of dried mango - Pablícia O. Galdino; Alexandre J. de M. Queiroz; Rossana M. F. de Figueirêdo; Ângela M. Santiago; Plúvia O. Galdino (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to determine the best osmotic dehydration (OD) condition for slices of mango cv. Espada through a factorial experiment, evaluating water loss and water activity during the process, and then perform convective drying at different temperatures to sensorially evaluate the obtained dried mango. An experiment was conducted in a 23 factorial experiment, with three central points, to evaluate the influence of thickness (1; 1.5 and 2 cm), sucrose concentration (35; 45 and 55 ºBrix) and temperature (30, 40 and 50 ºC) on water loss and water activity during the process. Convective drying was carried out in a tray dryer at temperatures of 50, 60 and 70 ºC, with an air speed of 1.5 m s-1. The optimal OD condition was found for slices with 1 cm thickness, sucrose concentration of 55 °Brix and temperature of 50 °C. Dried mangoes produced at temperatures of 50 and 60 °C were the most accepted among the tasters for the attributes of color, appearance, odor and taste, intensity of hardness, preference and purchase intention, and can be a promising alternative for utilization of Espada mango.